Computer simulation of air-conditioning system design and ducting analysis for professionals and engineering students (2001)
Air-conditioning system design and ducting analysis has over the years been an aspect of Engineering, which even though has developed greatly, yet it brings about very tedious tasks of analysis, low level of accuracy, and a lot of time input in carrying out its analysis manually. This work makes provision for the use of a software package, designed for ducting analysis. It has the capability of handling analysis for buildings having as much as nine (9) floors, with each floor having up to twenty (20) rooms. The report gives an account of the method used and the programming aspect of the package for ducting analysis. The thermal analysis of a building forms the basis for the equipment selection in terms of capacity of the cooling equipment, quantity of dehumidified air required and the type of system to be recommended. The estimated air quantity is then used in carrying out the analysis of the system. The package has been designed in such a way that results of analysis made could be printed out for use. Also, it can be easily used on any computer that has a floppy drive for its installation, and has been produced using Visual Basic 6.0. it would be very useful for professionals, as it can carry out analysis which might take hours to develop in few seconds, and also, can be used in higher institutions as teaching aid to INSTRUCT Engineering students.